2018
DOI: 10.1111/edt.12452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of loss of consciousness on maxillofacial fractures in simple falls

Abstract: Background/Aims Loss of consciousness while falling is reported to increase the risk of more severe injury. However, few studies of maxillofacial injuries have been reported. The aim of this study was to investigate the effects of loss of consciousness on maxillofacial fractures in falls on a level surface (simple falls). Material and Methods Patients with maxillofacial fractures caused by simple falls were subdivided into two categories: patients who fell without loss of consciousness and patients who fell wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 32 publications
1
20
2
Order By: Relevance
“…The association between falls and AC seems to be worth examining because falls are among the most frequent causes of facial bone fractures (Boffano et al, 2015b; Boffano, Kommers, Karagozoglu, & Forouzanfar, 2014). A simple fall is a fall that is not affected by height, because a fall from a height causes more severe injuries (Hino, Yamada, Araki, Kaneko, & Horie, 2019). Therefore, it is reasonable to think that a simple fall is a good example to compare the effects of AC on patients with falls.…”
Section: Introductionmentioning
confidence: 99%
“…The association between falls and AC seems to be worth examining because falls are among the most frequent causes of facial bone fractures (Boffano et al, 2015b; Boffano, Kommers, Karagozoglu, & Forouzanfar, 2014). A simple fall is a fall that is not affected by height, because a fall from a height causes more severe injuries (Hino, Yamada, Araki, Kaneko, & Horie, 2019). Therefore, it is reasonable to think that a simple fall is a good example to compare the effects of AC on patients with falls.…”
Section: Introductionmentioning
confidence: 99%
“…This seven-year exploratory study showed that traffic accidents are the main etiological agent of MFT, followed by falls, similar to what has been reported in other studies ( 2 , 3 , 5 - 8 , 13 - 24 ). Traffic accidents and falls are two of the leading causes of trauma worldwide, including MFT ( 1 , 5 , 7 , 9 - 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that traffic accidents and falls are the most prevalent etiologies of MFT ( 5 - 9 ). These etiologies represent real challenges both for the management of public policies targeting the care of this population through the implementation of primary care programs focused on the prevention of the main etiological factors and the factors associated with MFT and for the care professionals involved in the treatment of increasingly severe injuries ( 1 , 5 , 6 , 7 , 9 - 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of syncope, the occurrence of an injury is more frequent in cardiac syncope, in which a sudden "dead weight" fall occurs compared with reflex syncope where the decrease in blood pressure is usually slower resulting in a crumpling fall, usually accompanied by less injuries. Hino et al reported that patients with loss of consciousness and maxillofacial fractures tend to have more severe maxillofacial injuries than those without loss of consciousness (22). The absence of links between bone fracture and long-term prognosis (after exclusion from analysis of patients who died within 4 months) indicates that bone fracture should be considered a surrogate of other factors related to long-term survival and not directly determining survival.…”
Section: Discussionmentioning
confidence: 99%